2004
DOI: 10.1677/erc.0.0110191
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl transferase inhibitors: the next targeted therapies for breast cancer?

Abstract: The ras family of proto-oncogenes are upstream mediators of several essential cellular signal transduction pathways involved in cell proliferation and survival. Point mutations of ras oncogenes result in constitutively active Ras and have been shown to be oncogenic. However, ras activation can occur in the absence of ras mutations secondary to upstream receptor activation. The first important step in Ras activation is farnesylation by farnesyl transferase, and inhibitors of this enzyme have been demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 57 publications
1
21
0
1
Order By: Relevance
“…However, many potential substrates, independent of Ras, have been identified for farnesyl transferase inhibitors (FTIs), such as lamin A and human perioxisomal farnesylated protein, both of which have been used as surrogate markers of farnesylation, RhoB, cyclic guanosine monophosphate phosphodiesterase a, rhodopsin kinase and the g subunit of the retinal protein, transducin (O'Regan & Khuri 2004). The oral FTIs currently in clinical development are tipifarnib, lonafarnib and AZD3409 (Table 1).…”
Section: Farnesyl Transferase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many potential substrates, independent of Ras, have been identified for farnesyl transferase inhibitors (FTIs), such as lamin A and human perioxisomal farnesylated protein, both of which have been used as surrogate markers of farnesylation, RhoB, cyclic guanosine monophosphate phosphodiesterase a, rhodopsin kinase and the g subunit of the retinal protein, transducin (O'Regan & Khuri 2004). The oral FTIs currently in clinical development are tipifarnib, lonafarnib and AZD3409 (Table 1).…”
Section: Farnesyl Transferase Inhibitorsmentioning
confidence: 99%
“…Phase I studies of tipifarnib showed that continuous dosing was associated with severe toxicities, such as diarrhea, nausea, vomiting, renal dysfunction, and myelosuppression (O'Regan & Khuri 2004). A phase II study evaluated the activity of tipifarnib, as single agent, in endocrine-and/or chemotherapy-resistant patients with metastatic breast cancer .…”
Section: Tipifarnibmentioning
confidence: 99%
“…The Ras family of proto-oncogenes are upstream mediators of several essential cellular signal transduction pathways and, as such, provide a rational target for the treatment of malignancies (O'Regan and Khuri, 2004). Inhibitors of the enzyme farnesyl protein transferase prevent a key step in the post-translational processing of the RAS protein, and were developed initially as a therapeutic strategy to inhibit cell signalling in RAStransformed cells (Johnston, 2001).…”
Section: Farnesyl Transferase Inhibitorsmentioning
confidence: 99%
“…The ras proto-oncogene can activate downstream TK substrates (e.g., MAPK, MAPK/ERK kinase (MEK)) that influence cell proliferation, survival and apoptosis and has been implicated in breast cancer (O'Regan and Khuri, 2004). Farnesyl transferase inhibitors (e.g., tipifarnib, lonafarnib) were developed to inhibit tumour growth by blocking farnesylation, the first step in ras activation.…”
Section: Farnesyl Transferase Inhibitorsmentioning
confidence: 99%
“…Both in vitro and in vivo studies have shown that tipifarnib inhibits the growth of MCF-7 breast cancer tumours (O'Regan and Khuri, 2004), and a subsequent phase II study reported clinical benefit in 24% of women with endocrine-resistant metastatic breast cancer .…”
Section: Farnesyl Transferase Inhibitorsmentioning
confidence: 99%